Fluorofenidone Attenuates Oxidative Stress and Renal Fibrosis in Obstructive Nephropathy via Blocking NOX2 (gp91phox) Expression and Inhibiting ERK/MAPK Signaling Pathway - Jiao Qin; Wen-Juan Mei; Yan-Yun Xie; Ling Huang; Qiong-Jing Yuan; Gao-Yun Hu; Li-Jian Tao; Zhang-Zhe Peng (Karger Publishers, 2015)
Background/Aims: We evaluated the therapeutic effects of fluorofenidone (AKF-PD), a novel pyridone agent, targeting oxidative stress and fibrosis in obstructive nephropathy. Methods: AKF-PD was used to treat renal interstitial fibrosis in unilateral ureteral obstruction (UUO) obstructive nephropathy in rats. The expression of NOX2 (gp91phox), fibronectin and extracellular signal regulated kinase (ERK) were detected by western blot. A level of Malondialdehyde (MDA), an oxidative stress marker, was measured by ELISA. In addition, ROS and the expressions of NOX2, collagen I (a1), fibronectin and p-ERK were measured in angiotensin (Ang) II-stimulated rat proximal tubular epithelial cells (NRK-52E) in culture. Results: In NRK-52E cells, AKF-PD reduced AngII induced expressions of ROS, NOX2, fibronectin, collagen I (a1) and p-ERK. In UUO kidney cortex, AKF-PD attenuated the degree of renal interstitial fibrosis, which was associated with reduced the expressions of collagen I (a1) and fibronectin. Furthermore, AKF-PD downregulated the expressions of NOX2, MDA and p-ERK. Conclusion: AKF-PD treatment inhibits the progression of renal interstitial fibrosis by suppressing oxidative stress and ERK/MAPK signaling pathway.